Relationship of academic performance with learning techniques in students of dentistry of the radiology subject - Pérez Albela-García, Gretell (2021)
Objective. Determine the academic performance with learning techniques in dental students of the radiology subject. Materials and methods: The methodological design of the present study was of type: Observational, Analytical,  Prospective and Cross-sectional. It was made up of 80 students from the Faculty of Dentistry of the University of San Martín de Porres, who were enrolled in the academic semester 2018-II in the Radiology subject and who met the inclusion and exclusion criteria. Two evaluations were made: an evaluation applying the experience with seminars and an evaluation applying the experience with tutorials. Results: The application of the learning technique; tutorials or the application of tutorials plus seminars, cause different scores in the averages, before and after being applied, being reflected with the improvement of the grades after receiving any of the learning techniques. Conclusions: It was   shown that with the application of tutoring, grades were significantly improved in relation to tutorials plus seminars, which determined that the learning technique through tutorials influenced the academic performance of Radiology students.